SATELLITE NAVIGATION AND ITS IMPORTANCE IN TRANSPORTATION - Jurkovič, Martin; Adrien, Samuel (Perner's Contacts, 2016)
Satellite navigation systems have become nowadays very common and people can see them everywhere. Their use in transport is currently indispensable. Just the fact that navigation systems are very useful and necessary leads to the expansion of available systems. In the past, product selection for the user was easy and clear, because GPS was only one option. Currently, there are several satellite systems, but their number is constantly increasing.